2012
DOI: 10.1371/journal.pone.0037823
|View full text |Cite
|
Sign up to set email alerts
|

Dvl2-Dependent Activation of Daam1 and RhoA Regulates Wnt5a-Induced Breast Cancer Cell Migration

Abstract: BackgroundThe Dishevelled (Dvl) and Dishevelled-associated activator of morphogenesis 1 (Daam1) pathway triggered by Wnt5a regulates cellular polarity during development and tissue homoeostasis. However, Wnt5a signaling in breast cancer progression remains poorly defined.Methodology/Principal FindingsWe showed here that Wnt5a activated Dvl2, Daam1 and RhoA, and promoted migration of breast cancer cells, which was, however, abolished by Secreted Frizzled-related protein 2 (sFRP2) pretreatment. Dominant negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
117
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 61 publications
5
117
0
Order By: Relevance
“…Noncanonical Wnt proteins, such as Wnt5a, bind to different frizzled (Fzd) family members, including and Fzd7 (21,26), and coreceptors such as Ror2, Ryk, and PTK7 (27,28). In the PCP pathway, binding of Wnt ligand and its receptor complex leads to assembly of disheveled protein (Dvl) and its effector proteins, including disheveledassociated activator of morphogenesis 1 (DAAM1) (29)(30)(31). They then regulate cytoskeleton organization and cell migra-tion through Rho GTPases such as RhoA, Rac1, and Cdc42 (30)(31)(32)(33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Noncanonical Wnt proteins, such as Wnt5a, bind to different frizzled (Fzd) family members, including and Fzd7 (21,26), and coreceptors such as Ror2, Ryk, and PTK7 (27,28). In the PCP pathway, binding of Wnt ligand and its receptor complex leads to assembly of disheveled protein (Dvl) and its effector proteins, including disheveledassociated activator of morphogenesis 1 (DAAM1) (29)(30)(31). They then regulate cytoskeleton organization and cell migra-tion through Rho GTPases such as RhoA, Rac1, and Cdc42 (30)(31)(32)(33).…”
mentioning
confidence: 99%
“…In the PCP pathway, binding of Wnt ligand and its receptor complex leads to assembly of disheveled protein (Dvl) and its effector proteins, including disheveledassociated activator of morphogenesis 1 (DAAM1) (29)(30)(31). They then regulate cytoskeleton organization and cell migra-tion through Rho GTPases such as RhoA, Rac1, and Cdc42 (30)(31)(32)(33). Although the function of noncanonical Wnt signaling in the cornea is unclear, robust expression of Wnt5a can be observed in fetal but not adult human corneal endothelium (34).…”
mentioning
confidence: 99%
“…In addition, Wntmediated cell signalling plays a unique role in the cancer proliferation and cancer differentiation. It has been reported that that Wnt5a promotes the cancer metastasis and proliferation in various malignant tissues including breast, melanoma, gastric and liver cancer (Zhu et al, 2012). Keeping all this facts in mind, present study was designed to investigate the effect of Wnt on osteosarcoma cancer cells including U2OS and SaOS-2 cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt5a has been demonstrated to exert differential effects on cancer development [5]. Wnt5a can promote cancer progression and metastasis in malignant melanoma, breast cancer, and gastric cancer [19][20][21][22][23]. However, some evidence supports the hypothesis that Wnt5a acts as a tumor suppressor in certain experimental systems [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%